Physiological Basis of the Couvade Syndrome and Peripartum Onset of Bipolar Disorder in a Man: A Case Report and a Brief Review of the Literature - Giourou, Evangelia; Skokou, Maria; Andrew, Stuart Peter; Gourzis, Philippos (Frontiers in Psychiatry, 2018)
Rapid hormonal changes during pregnancy as well as psycho-social stressors accompanying parenthood have often been associated with peripartum mood episodes in women with bipolar disorder or with not yet clinically expressed bipolar diathesis. Yet, little is known about the correlation of peripartum onset of bipolar disorder in men. We present the case of a man with bipolar disorder with peripartum onset and subsequent episodes following the peripartum initiation of the disease, as well as the association of the couvade syndrome, as a pathological response to a man due to hormonal shifts observed in males cohabiting with a pregnant female. There is a well-known correlation between the peripartum period and mood disturbances to the point of inducing full blown episodes, suggesting of a bipolar disorder initiation or mood episodes relapsing in female patients already diagnosed with bipolar disorder. It seems though, that males are not less influenced by hormonal and psycho-social factors posed upon them during the peripartum period of their cohabiting female spouse.